Technological response of wild macaques (Macaca fascicularis) to anthropogenic change. - Luncz, LV; Svensson, MS; Haslam, M; Malaivijitnond, S; Proffitt, T; Gumert, MD (Springer, 2017)
Anthropogenic disturbances have a detrimental impact on the natural world; the vast expansion of palm oil monocultures is one of the most significant agricultural influences. Primates worldwide consequently have been affected by the loss of their natural ecosystems. Long-tailed macaques (Macaca fascilularis) in Southern Thailand have, however, learned to exploit oil palm nuts using stone tools. Using camera traps, we captured the stone tool behavior of one macaque group in Ao Phang-Nga National Park. Line transects placed throughout an abandoned oil palm plantation confirmed a high abundance of nut cracking sites. Long-tailed macaques previously have been observed using stone tools to harvest shellfish along the coasts of Thailand and Myanmar. The novel nut processing behavior indicates the successful transfer of existing lithic technology to a new food source. Such behavioral plasticity has been suggested to underlie cultural behavior in animals, suggesting that long-tailed macaques have potential to exhibit cultural tendencies. The use of tools to process oil palm nuts across multiple primate species allows direct comparisons between stone tool using nonhuman primates living in anthropogenic environments.